2018
DOI: 10.1111/bre.12281
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the depocenters and the basement structure, below the central Chile Andean Forearc: A 3D geophysical modelling in Santiago Basin area

Abstract: Since the last century, several geological and geophysical studies have been developed in the Santiago Basin to understand its morphology and tectonic evolution. However, some uncertainties regarding sedimentary fill properties and possible density anomalies below the sediments/basement boundary remain. Considering that this is an area densely populated with more than 6 million inhabitants in a highly active seismotectonic environment, the physical properties of the Santiago Basin are important to study the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Most of the forearc became a positive, mountainous area as indicated by seismic, borehole, and gravimetric data that show an irregular paleorelief carved on Oligo-Miocene and older rocks (e.g., García, 1968;Rubio, 1990;Elgueta et al, 2000;Yáñez et al, 2015;González et al, 2018). The difference in elevation between the lowest and the highest parts of this paleorelief is approximately 1000 m (see González et al, 2018). Sedimentation resumed in the forearc during the lower Pliocene (Fig.…”
Section: Implications On the Evolution Of The West Andean Thrustmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the forearc became a positive, mountainous area as indicated by seismic, borehole, and gravimetric data that show an irregular paleorelief carved on Oligo-Miocene and older rocks (e.g., García, 1968;Rubio, 1990;Elgueta et al, 2000;Yáñez et al, 2015;González et al, 2018). The difference in elevation between the lowest and the highest parts of this paleorelief is approximately 1000 m (see González et al, 2018). Sedimentation resumed in the forearc during the lower Pliocene (Fig.…”
Section: Implications On the Evolution Of The West Andean Thrustmentioning
confidence: 99%
“…Plio-Pleistocene deposits in the forearc have highly variable thicknesses that reach more than 2000 m. Thus, the accommodation space cannot have been created by a global sea-level rise and the consequent fluvial sedimentation to maintain river equilibrium profile since maximum eustatic sea-level changes during the last 5 Ma are just on the order of 100 m (Haq et al, 1987). In addition, González et al (2018) noted that the lowest part of the paleorelief carved in Oligo-Miocene or older rocks in central Chile is located at elevations of 200 m below the present sea level, which indicates that the Central Depression has been subjected to subsidence. Information from ENAP wells in the Central Depression between ~41 • and 42 • S show that the thickness of Plio-Pleistocene deposits increases considerably to the east and reaches ~2250 m near the limit with the Andean Cordillera (Fig.…”
Section: Implications On the Evolution Of The West Andean Thrustmentioning
confidence: 99%
“…9. Results of inversion products were effectively located with porphyry copper sulphide mineralization data, and density and magnetics susceptibility distribution have good spatial correlations (Gonzalez, et al, 2018) with copper mineralization. In the next section, the results of the study are considered in terms of sections AA and BB shown in Fig.…”
Section: Geophysical Inversion Of Groundmentioning
confidence: 98%
“…The Central Depression basin is filled with Pleistocene to Holocene sedimentary and volcaniclastic deposits (e.g., Fock et al, 2005). Geophysical studies have inferred an average depth of 250 m for the Central Depression in the vicinity of Santiago, with a maximum depth of 500 m (González et al, 2018;Yáñez et al, 2015). The geology of the western flank of the Main Cordillera is dominated by volcanic and sedimentary rocks of the Abanico Formation (Late Eocene to Early Miocene), which is overlain by the volcanic Farellones Formation (Miocene).…”
Section: Geological and Geophysical Frameworkmentioning
confidence: 99%
“…Although some seismicity clusters suggest the likely presence of east dipping faults closer to the western flank of the Main Cordillera (see, e.g., Armijo et al, 2010;Farías et al, 2010), there are no records of clear seismic clustering along the trace of the SRF at depths <5 km (see the discussion in Estay et al, 2016). Gravimetric studies have indicated the presence of a sediment depocenter in the northeastern part of the Santiago basin, whose eastern margin partially coincides with the northern segment of the SRF (González et al, 2018;Yáñez et al, 2015). However, these studies do not show any distinctive feature in the structure of the basin along the central and southern segments of the SRF, suggesting that the SRF did not play a key role in the development of the Santiago basin (Yáñez et al, 2015).…”
Section: 1029/2020tc006294mentioning
confidence: 99%